Perlindungan Hukum Karyawan PT. Arta Sedana Retailindo yang Terkena Pemutusan Hubungan Kerja atas Klaim BPJS Ketenagakerjaan - I Made Anggra; I Putu Gede Seputra; Luh Putu Suryani (Warmadewa Press, 2020)
Labor protection laws should provide a sense of security for workers at work, or in other words, workers may no more need to worry about working. One of the problems with workers regarding their rights contained in Social Security Administration Body for Manpower (BPJS Ketenagakerjaan) is when a termination of employment (PHK) occurs. In this regard, the research examines two issues: the form of legal protection for employees of PT. ASR imposed PHK related to BPJS Ketenagakerjaan claims and law enforcement that could be taken by the laid-off employees in question. This study aims to examine the form of legal protection and law enforcement efforts taken by employees who have been laid off due to BPJS Ketenagakerjaan claims. This research is an empirical legal research with a sociological approach. The research was conducted at PT. ASR and data were obtained from interviews and statutory studies. The results showed the legal protection for laid-off workers is set forth in the work contract and the labor participation in the BPJS Ketenagakerjaan refers to Law No. 13 of 2003 Article 156 paragraphs (1), (2), (3) and (4), Law No. 24 of 2011 of BPJS Ketenagakerjaan and law enforcement efforts undertaken are in the form of preventive and repressive forms. The corporates employing workers, in terminating the employment of employees, should absolutely not override their obligations which are the rights of their employees.